Cost of injury care in India: cross-sectional analysis of National Sample Survey 2014. Issue 2 (19th July 2017) - Tripathy, JP; Jagnoor, J; Prasad, BM; Ivers, R
Abstract : Background: Injuries account for nearly 10% of total deaths in India and this burden is likely to rise. We aimed to estimate the out-of-pocket (OOP) expenditure and catastrophic expenditure due to hospitalisation or outpatient care as a result of any injury and factors associated with incurring catastrophic expenditure. Methods: Secondary analysis of nationally representative data for India collected by National Sample Survey Organization in 2014, reporting on health service utilisation and healthcare-related OOP expenditure by income quintiles and by type of health facility (public or private). Results: The median expenditure per episode of hospitalisation due to any injury was US$156, and it was three times higher among the richest quintile compared with the poorest quintile (p<0.001). There was a significantly higher prevalence (p<0.001) of catastrophic expenditure among the poorest quintile (32%) compared with the richest (21%). Mean private sector OOP hospitalisation expenditure was five times higher than in the public sector (p<0.001). Medicines accounted for 37% and 58% of public sector hospitalisation and outpatient care, respectively. Patients treated in a private facility, hospitalised for over 7 days, in the poorest wealth quintiles and of general caste had higher odds of incurring catastrophic expenditure. Conclusion: People who sustain an injury have a high risk of catastrophic household expenditure, particularly for those in lowest income quartiles. There is a clear need for publicly funded risk protection mechanisms targeting the poor. Promotion of generic medicines and subsidisation for the poorest wealth quintile may also reduce OOP expenditure in public sector facilities.